Diplopia; an Adverse Effect of Citalopram - Seyed Hamzeh Hosseini; Amirhossein Ahmadi (Mazandaran University of Medical Sciences, 2019)
Citalopram, a selective serotonin reuptake inhibitor (SSRI), was approved by the Food and Drug Administration in 1998 as a safe and well-tolerated antidepressant; the use of it may result in rare and sometimes dangerous side effects. Diplopia is a rare adverse effect of citalopram that comes with double vision and disrupts daily living. Currently, only two cases of citalopram-related diplopia have been internationally reported. The current paper presents a third reported case of diplopia following citalopram use in a healthy subject. A 47-year-old man involved in an accident was subsequently affected by serious depression. Following 6 months of a 40-mg daily dose of citalopram, the patient complained of itchy irritated eyes and double vision symptomatic of diplopia. He was referred to an eye specialist, who confirmed no apparent problems following an examination of the eye. After a decrease in the dose of citalopram, the eye symptoms steadily decreased and eventually disappeared. The rapid disappearance of diplopia subsequent to the discontinuing use of citalopram suggests an association between the adverse reaction and the medicine. As a result, it is recommended that physicians inform patients of the possibility of induction of diplopia related to the use of citalopram and other SSRIs. In the future, the prescription of SSRIs at higher doses may be ordered with and on the recommendation of patients, who have been aware of the risks of the drug.